Wordsworth after war : recovering peace in the later poetry - Shaw, Philip, 1965- (Cambridge ; New York, NY : Cambridge University Press, 2023)
William Wordsworth's later poetry complicates possibilities of life and art in war's aftermath. This illuminating study provides new perspectives and reveals how his work following the end of the revolutionary and Napoleonic wars reflects a passionate, lifelong engagement with the poetics and politics of peace. Focusing on works from between 1814 and 1822, Philip Shaw constructs a unique and compelling account of how Wordsworth, in both his ongoing poetic output and in his revisions to earlier works, sought to modify, refute, and sometimes sustain his early engagement with these issues as both an artist and a political thinker. In an engaging style, Shaw reorients our understanding of the later writings of a major British poet and the post-war literary culture in which his reputation was forged. This title is part of the Flip it Open Programme and may also be available Open Access. Check our website Cambridge Core for details.
Conscripting 'The Recluse' -- Peace out of time : The White Doe of Rylstone -- Thanksgiving after war -- 'Returning, like a ghost unlaid' : Peter Bell and The Waggoner -- Violent waters : The River Duddon and Ecclesiastical Sketches -- Wordsworth After Byron : Memorials of a Tour on the Continent, 1820 -- After Wordsworth.
Title from publisher's bibliographic system (viewed on 10 Jul 2023).
Keywords: Wordsworth, William, -- 1770-1850 -- Criticism and interpretation; Peace in literature; English poetry -- 19th century -- History and criticism